2009
DOI: 10.2353/ajpath.2009.080625
|View full text |Cite
|
Sign up to set email alerts
|

Chloride Intracellular Channel Protein-4 Functions in Angiogenesis by Supporting Acidification of Vacuoles Along the Intracellular Tubulogenic Pathway

Abstract: Endothelial cells form capillary tubes through the process of intracellular tubulogenesis. Chloride intracellular channel (CLIC) family proteins have been previously implicated in intracellular tubulogenesis, but their specific role has not been defined. In this study, we show that disruption of the Clic4 gene in mice results in defective angiogenesis in vivo as reflected in a Matrigel plug angiogenesis assay. An angiogenesis defect is also apparent in the retina, both in the decreased spontaneous development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
118
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(131 citation statements)
references
References 41 publications
(47 reference statements)
6
118
0
Order By: Relevance
“…It has been argued that CLICs might not function as Cl 2 channels because the better characterized inhibitors SIDS or DIDS are without effect on CLIC ion conductance (Jentsch et al, 2002). However, in keeping with CLIC-mediated Cl 2 ion conductance, a role in vacuolar and/or vesicular acidification has been reported for CLIC5B in osteoclasts (Edwards et al, 2006), for CLIC1 in macrophages (Jiang et al, 2012) and for CLIC4 in endothelial cells (Ulmasov et al, 2009). Here, we observed that the effect of CLIC5A on ERM phosphorylation was not inhibited by extracellular IAA-94 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It has been argued that CLICs might not function as Cl 2 channels because the better characterized inhibitors SIDS or DIDS are without effect on CLIC ion conductance (Jentsch et al, 2002). However, in keeping with CLIC-mediated Cl 2 ion conductance, a role in vacuolar and/or vesicular acidification has been reported for CLIC5B in osteoclasts (Edwards et al, 2006), for CLIC1 in macrophages (Jiang et al, 2012) and for CLIC4 in endothelial cells (Ulmasov et al, 2009). Here, we observed that the effect of CLIC5A on ERM phosphorylation was not inhibited by extracellular IAA-94 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…CLIC4 has been found to be localized to vesicles in human umbilical vein endothelial cells (Bohman et al 2005) and large vacuoles in mouse heart endothelial cells (Ulmasov et al 2009). In vitro, CLIC4 promotes endothelial proliferation, network formation, capillary-like sprouting, and lumen formation (Tung et al 2009).…”
Section: Jj Tung Et Almentioning
confidence: 99%
“…In vitro, CLIC4 promotes endothelial proliferation, network formation, capillary-like sprouting, and lumen formation (Tung et al 2009). Analyses of retinal vasculature in developing mice, and in adult mice challenged by an oxygen toxicity assay, reveals stunted vascular development in clic4 2/2 mice (Ulmasov et al 2009). CLIC4 may also influence vacuolar formation in endothelial cells by regulating pH (Ulmasov et al 2009).…”
Section: Jj Tung Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the stromal fibroblast is an attractive target for therapeutic intervention. CLIC4 promotes proliferation and vascular tubulogenesis of endothelial cells in the formation of new blood vessels (23,30). Here, we found that treatment of fibroblasts with the agents blocking CLIC4 had a marked repressive effect on the production of angiogenic factors associated with myofibroblast transdifferentiation, indicating that inhibiting the CLIC4 might have therapeutic potential targeting tumour stroma.…”
Section: Discussionmentioning
confidence: 72%